Comparison of ATPase-Encoding Type III Secretion System hrcN Genes in Biocontrol Fluorescent Pseudomonads and in Phytopathogenic Proteobacteria - Rezzonico, Fabio (American Society for Microbiology, 2004)
Type III protein secretion systems play a key role in the virulence of many pathogenic proteobacteria, but they also occur in nonpathogenic, plant-associated bacteria. Certain type III protein secretion genes (e.g., hrcC) have been found in Pseudomonas sp. strain SBW25 (and other biocontrol pseudomonads), but other type III protein secretion genes, such as the ATPase-encoding gene hrcN, have not been found. Using both colony hybridization and a PCR approach, we show here that hrcN is nevertheless present in many biocontrol fluorescent pseudomonads. The phylogeny of biocontrol Pseudomonas strains based on partial hrcN sequences was largely congruent with the phylogenies derived from analyses of rrs (encoding 16S rRNA) and, to a lesser extent, biocontrol genes, such as phlD (for 2,4-diacetylphloroglucinol production) and hcnBC (for HCN production). Most biocontrol pseudomonads clustered separately from phytopathogenic proteobacteria, including pathogenic pseudomonads, in the hrcN tree. The exception was strain KD, which clustered with phytopathogenic pseudomonads, such as Pseudomonas syringae, suggesting that hrcN was acquired from the latter species. Indeed, strain KD (unlike strain SBW25) displayed the same organization of the hrpJ operon, which contains hrcN, as P. syringae. These results indicate that the occurrence of hrcN in most biocontrol pseudomonads is not the result of recent horizontal gene transfer from phytopathogenic bacteria, although such transfer might have occurred for a minority of biocontrol strains.